E-learning using learning management system - Regina Kulvietienė; Genadijus Kulvietis; Irma Šileikienė; Jelena Stankevič (Lietuvos Matematikos Rinkinys)
Learning management systems (LMS) have become the mainstream technology underlying corporate training and the migration to e-learning. A great number of LMS provides integrated services such as the designing and development of on-line learning contents, the communication and collaboration between the learners and teachers, event scheduling, creation of test questions and test administration. LMS plays a key role in the e-learning environment.